Comparison of Efficacy and Safety of Atropine Sulphate and Glycopyrrolate in the Treatment of Organophosphorus Poisoning at St. Martha's Hospital, Bangalore. - N, Anju; Rani RH, Shobha; P, Nalini (Indian Journal of Pharmacy Practice)
Organophosphorus poisoning (OP) is the most common poisoning in India because of their easy availability. Atropine is considered the drug of choice in the management of OP poisoning and continues to be the standard treatment .Glycopyrrolate is a synthetic quaternary amine, a medication of the muscarinic anticholinergic group, with peripheral effects similar to those of atropine. The objective of this study was to compare the efficacy and safety of Atropine and Glycopyrrolate on OP poisoning patients. A total of 33 patients were enrolled in the study. All patients were recruited into two groups and accordingly received either Atropine or Glycopyrrolate as per the recognized dosing schedule as practiced in the hospital. The details of each OP poisoning case was observed and collected in the data collection form and assessed. All 33 patients were admitted to the ICU and the duration of hospital stay ranged from 2 to 21 days the mean ICU stay in Group-A was 5.43±2.50, in Group-B was 6.42±5.13 (P=0.511). In Group-A, 40 patients required ventilation, whereas 40% did not and in Group-B, 36.85% required ventilation, and 63.15% did not (P=0.304). Among the ADRs documented the most prominent one was Altered Sensorium seen in 64.28% cases in Group-A (P<0.001) whereas in Group-B none had Altered sensorium. The total cost for the anticholinergic treatment in Group-A ranged from 43 rupees to 1503 rupees and in Group-B it was 639 rupees to 4032 rupees (P<0.001) . 3 patients expired, two out of which 2 were from Group-A. The study revealed that both the groups had the same efficacy, but Atropine showed a very distinct CNS toxicity and Glycopyrrolate being a relatively expensive drug.
Keywords: Organophosphorus poisoning; Atropine; Glycopyrrolate; safety; efficacy; expensive; toxicity